Ten month outcome of cognitive behavioural therapy v. interpersonal psychotherapy in patients with major depression: a randomised trial of acute and maintenance psychotherapy. Issue 14 (9th May 2017) - Mulder, R.; Boden, J.; Carter, J.; Luty, S.; Joyce, P.
Abstract : Background: Cognitive behaviour therapy (CBT) and interpersonal psychotherapy (IPT) are the most studied psychotherapies for treatment of depression, but they are rarely directly compared particularly over the longer term. This study compares the outcomes of patients treated with CBT and IPT over 10 months and tests whether there are differential or general predictors of outcome. Methods: A single centre randomised controlled trial (RCT) of depressed outpatients treated with weekly CBT or IPT sessions for 16 weeks and then 24 weeks of maintenance CBT or IPT. The principle outcome was depression severity measured using the MADRS. Pre-specified predictors of response were in four domains: demographic depression, characteristics, comorbidity and personality. Data were analysed over 16 weeks and 40 weeks using general linear mixed effects regression models. Results: CBT was significantly more effective than IPT in reducing depressive symptoms over the 10 month study largely because it appeared to work more quickly. There were no differential predictors of response to CBT v . IPT at 16 weeks or 40 weeks. Personality variables were most strongly associated with overall outcome at both 16 weeks and 40 weeks. The number of personality disorder symptoms and lower self-directness and reward dependence scores were associated with poorer outcome for both CBT and IPT at 40 weeks. Conclusions: CBT and IPT are effective treatments for major depression over the longer term. CBT may work more quickly. Personality variables are the most relevant predictors of outcome.